(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Fire behavior of textiles varies depending on fiber composition, manufacturing process and any additional treatments applied. Such variables can contribute to significant differences in the flammability making it difficult to estimate the risk of fire ignition. Clothing fires can cause burns with minor injuries and burns leading to serious injuries that may require hospitalization. The elderly and children are especially at risk since they may not recognize the dangers of a clothing fire and how to react quickly to extinguish the flames. Health and safety professionals are frequently asked to recommend reducing such risks. However, information about the flammability properties of non-FR treated clothing worn by the public is generally not available. The objective of this research program was to develop a simplified method for defining the flammability of commercially available fabrics. 50 samples were tested including Cotton, Wool, Silk, Nylon and Polyester. Changes in the weight of a sample resulting from combustion including the time involved in the combustion cycle was used as a indictor of the total heat generated by the fire and the risk and severity of a burn injury. The results showed that the Cotton and Wool fabric samples created the highest risk of burn injury while the Polyester fabric created the lowest risk. These conclusions are based on two criteria: Total time associated with a combustion cycle and the loss of fabric mass during the combustion cycle. The proposed method can be carried out using a standard laboratory fume-hood, a precision weight scale and a stopwatch.